MENUMBUHKAN KEDISIPLINAN MELALUI PENERAPAN REWARD AND PUNISHMENT DALAM KULTUR SEKOLAH PESANTREN - Adi Kusmanto; Rohim Habibi; Susanti Susanti (IAI Al Muhammad Cepu, 2024)
In the world of education, discipline is often ignored by students. Even though the school has installed and implemented school rules, in fact there are still students who behave less than disciplined. This research aims to determine the application of reward and punishment in the learning process in strengthening disciplined character. This research uses a qualitative approach with a case study type. Data collection methods use interviews, observation and documentation. The results of this research are that in its application MI Al Urwatul Wutsqo 1 Jombang gives a reward when a child performs a good action and gives punishment when a child performs an action that violates the rules and regulations. The application of the Reward and Punishment method at MI Al Urwatul Wutsqo 1 Jombang always takes into account the situation and conditions so that rewards and punishment are given according to needs. The forms of reward given are verbal and non-verbal rewards, while punishment is also the same, the teacher gives verbal punishment in the form of a verbal warning, and non-verbal punishment in the form of writing down the student's name in the violation book followed by mental development by calling the student's parents and memorizing several letters in Al-Qur'an, praying and reading prayers as well as cleaning classrooms, sweeping the madrasa yard and bathrooms. Apart from that, an effort to assess the success of rewards and punishment in shaping students' disciplinary character is to use process evaluation, namely an assessment carried out during the learning process by observing students' daily attitudes when they are in the madrasah environment.